Representational distance between expert narration and local accounts: A reflection on the politics of evidence in the field of memory in Colombia [Distância representacional entre a narrativa especializada e os relatos locais: Uma reflexão sobre as políticas da evidência no campo da memória na Colômbia] [Distancia representacional entre la narración experta y los relatos locales: Una reflexión sobre las políticas de la evidencia en el campo de la memoria en Colombia] (2020)
The paper analyzes the epistemological limits of the narration resulting from the specialized work on memory. It is based, on the one hand, on fieldwork carried out in the stilt villages of Ciénaga Grande de Santa Marta (Colombia) between 2017 and 2018. The focus of the fieldwork was the local reception of the National Centre for Historical Memory (CNMH) report, published in 2014, on the paramilitary massacres that had occurred in that area. And, on the other, on the research team’s participation in the writing of the CNMH report on anti-personnel mines in 2017. The strength of the text, a dialectical exercise between the anthropology of violence and the hermeneutical phenomenology, rests on it being a self-critical piece of work written from within the expert system. We propose the existence of a necessary representational distance (not contingent) between the account as a form of local expression and its translation into a narration that is projected outside the context in which local stories are produced. The article concludes that, beyond the very experience of violence represented in such accounts, it is the logic of the expert system that draws the contours of the politics of evidence in the field of memory. © 2020, Universidad de los Andes, Bogota Colombia. All rights reserved.